Relativity : the special and the general theory - Albert Einstein (New Delhi Finger Print Classics, 2019)
Relativity: The Special and the General Theory is a groundbreaking scientific work written by Albert Einstein, one of the most renowned physicists of all time. Published in 1915, the book revolutionized our understanding of space, time, and gravity. Relativity remains a cornerstone of modern physics and a testament to Einstein$1 (Bs intellectual brilliances
Keywords: Special Theory; General Theory